Implications of Blood Coagulation and Fibrinolytic Disorders in Severe Endometritis-Pyometra Complex in Bitches - Radwińska Justyna (Bulletin of the Veterinary Institute in Pulawy, 2012)
Twenty bitches with acute endometritis-pyometra complex (EPC) and 20 clinically healthy bitches were examined. The following coagulation parameters were determined in haemostatic evaluations: prothrombin time (PT), activated partial thromboplastin time (aPTT), thrombin time (TT), fibrinogen concentrations (FBG), D-dimer concentrations (D-D), antithrombin activity (AT), and blood platelet counts (PLT). Morphological and biochemical blood parameters were also analysed. Examinations of animals affected by EPC revealed blood coagulation and fibrinolytic disorders, and the noted results (PT 13.7 ±1.06 s, aPTT 23.4 ±1.04 s, TT 15.6 ±0.68 s, FBG 2.2 g/L, D-D 785.4 ±103.05 μg/L, AT 111.1 ±13.51%, PLT 169.30 ±126.31 103/μL) point to a high risk of disseminated intravascular coagulation. The findings indicate that the coagulation parameters of bitches affected by EPC should be analysed before treatment as the noted disorder can significantly complicate therapy and ovariohysterectomy, and endanger the patients' life.